Social landscapes: social interaction fostering a healthier lifestyle - Pitt-Perez, Olivia (Kansas State University, 2014)
It is easier for users to say that they frequent a park because they like the greenery than to say instead, that a park offers opportunities to meet or watch other people (Marcus, 1998).One of the main reasons people visit parks is to engage in both overt and covert social interaction (Gehl, 2010). Many people desire the opportunity to interact with others as a means of fulfilling their social well-being, but it is often unattainable in a civic space due to the lack of activities that promote social interaction. The lack of activities is specifically relevant in and around Washington Square Park, primarily due to a series of physical and social dilemmas the site faces. Washington Square Park is an underused civic space that has the potential to establish itself as a social civic anchor for downtown Kansas City, Missouri. Developing Washington Square Park into a civic space that promotes social interaction will help to achieve this potential. It will also help to bridge the gap with the current physical and social dilemmas that hinder the space. Through a process of literature review, precedent studies, and site analysis, project goals were established. To achieve these goals a set of design interventions were formed to address the physical and social dilemmas in and around the site. These interactions will then inform a final design for Washington Square Park that promotes a healthier lifestyle through social interaction for the users of the site.
Keywords: Social Interaction; Civic Space; Urban Design; Landscape Architecture (0390)